Corrigendum to ‘Exposure to the Polychlorinated biphenyl mixture Aroclor 1254 elicits neurological and cardiac developmental effects in early life stage zebrafish (Danio rerio)’ [Chemosphere 371 (2025), 144023] - Corey S. Green; Jeffrey M. Morris; Jason T. Magnuson; Rachel Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Daniel Schlenk; Aaron P. Roberts (Chemosphere, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Aroclor 1254 impairs visual and neurosensory signaling pathways independent of the aryl hydrocarbon receptor in larval zebrafish - Jason T. Magnuson; Corey S. Green; Jeffrey M. Morris; Rachel R. Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Aaron P. Roberts; Daniel Schlenk (Aquatic Toxicology, 2026)

Aridification Shaped the Diversification of Bothriembryon Land Snails in a Global Biodiversity Hotspot - Frank Köhler; Corey S. Whisson; Nerida G. Wilson; Andrew M. Hosie; Abraham S. H. Breure; Lisa A. Kirkendale (Journal of Biogeography, 2025)
Aim Resolving the spatio‐temporal diversification patterns and systematic relationships of endemic Australian land snails against the backdrop of Neogene aridification through analyses of a combined nuclear and mitochondrial DNA sequence dataset. Location Western Australia. Taxon Mollusca, Stylommatophora, Bothriembryontidae, Bothriembryon. Methods We employed Bayesian Inference and Maximum Likelihood to reconstruct the phylogenetic relationships in a group of Australian land snails using mitochondrial (COI, 16S) and nuclear (ANT) DNA sequences. Divergence times have been estimated by employing optimised molecular clocks using BEAST2, and RelTime in MEGA12. Speciation and net‐diversification rates have been modelled using revBayes to visualise diversification dynamics in lineage‐through‐time (LTT) plots. We employed automated species delimitation methods ASAP and bPTP to estimate taxonomic diversity. Results Our final sequence dataset contained 1052 new DNA sequences from 374 individuals, representing 97% of all accepted species plus 26 putatively new species based on morphology and distribution. Recognizing almost three times as many candidate species, both DNA‐based species delimitation methods have excessively inflated diversity estimates, casting doubt on the usefulness of these methods in groups with marked phylogeographic structure. Nine well‐supported principal clades were recovered. Fossil‐calibrated chronograms revealed an early bifurcation of Bothriembryon followed by an accumulation of lineages over time. LTT plots revealed a relative flattening of the speciation curve from 15 to 10 Ma on. However, we also detected a steep increase in intraspecific lineage diversification during the last approx. 1 Ma. The modeled speciation and net diversification rates have continuously declined over the last 25 Ma, while extinction rates have remained relatively steady until about 5 Ma, when they also started to climb. Main Conclusions Declining diversification rates during much of the Neogene, followed by increasing extinction rates, coincided with increasing aridity throughout Western Australia. A more recent increase in lineage diversification rates, driven by intraspecific differentiation, coincides with the rise of mesic conditions since the end of the Pleistocene. Both trends imply that through influencing extinction and diversification rates, historical climate change has likely contributed to shaping the current distribution patterns in Bothriembryon land snails that are characterised by fragmentation. Moreover, by uncovering many undescribed taxa, including multiple short‐range endemics, this study highlights the importance of continued conservation efforts in this globally important biodiversity hotspot. Key habitats, such as lithorefugia, in an otherwise harsh and exposed landscape are important strongholds for Bothriembryon to weather the impact of aridification.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Corrigendum to ‘Exposure to the polychlorinated biphenyl mixture Aroclor 1254 elicits neurological and cardiac developmental effects in early life stage zebrafish (Danio rerio)’ [Chemosphere 371(2025):144023] - Corey S. Green; Jeffrey M. Morris; Jason T. Magnuson; Rachel Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Daniel Schlenk; Aaron P. Roberts (Chemosphere, 2025)

Exposure to the Polychlorinated biphenyl mixture Aroclor 1254 elicits neurological and cardiac developmental effects in early life stage zebrafish (Danio rerio) - Corey S. Green; Jeffrey M. Morris; Jason T. Magnuson; Rachel R. Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Daniel Schlenk; Aaron P. Roberts (Chemosphere, 2025)

In Pursuit of Conference Equity - Isabel Martínez-Farrington; Loraine Bonet; Aixa Alemán-Díaz; Justin Ballenger; Dwight Ebanks; Mona Behl; Sarah Kolesar; Sharon Cooper; Corey Garza; Jonathan Lewis; Brandon Jones; Lisa White (Oceanography, 2024)
Scientific meetings and conferences are a cornerstone of scientific culture. By bringing people together around a shared purpose, meetings serve as a platform for knowledge exchange and can often foster a sense of belonging. As some will argue, conferences can become “counterspaces” to affirm a person’s identity, provided they have adequate access to resources and support (Nakajima et al., 2024). From students to retirees, scientific meetings and conferences provide engagement and professional development opportunities for people from various career tracks and stages and serve as engines of innovation and collaboration. As a major source of revenue, meetings and conferences are also integral to the business models of many professional societies, publishers, exhibitors, businesses, and local economies.

An integrated assessment of the 1,4-dioxane cancer mode of action and threshold response in rodents - Mark Lafranconi; Janet Anderson; Robert Budinsky; Lisa Corey; Norman Forsberg; Joanna Klapacz; Matthew J. LeBaron (Regulatory Toxicology and Pharmacology, 2023)

Phylogenetic assessment of the halophilic Australian gastropod Coxiella and South African Tomichia resolves taxonomic uncertainties, uncovers new species and supports a Gondwanan link - Angus D'Arcy Lawrie; Jennifer Chaplin; Lisa Kirkendale; Corey Whisson; Adrian Pinder; Musa C. Mlambo (Molecular Phylogenetics and Evolution, 2023)

Changing the Culture of Coastal, Ocean, and Marine Sciences: Strategies for Individual and Collective Actions - Mona Behl; Sharon Cooper; Corey Garza; Sarah Kolesar; Sonya Legg; Jonathan Lewis; Lisa White; Brandon Jones (Oceanography, 2021)
Geoscience is plagued with structural and systemic barriers that prevent people of historically excluded groups from fully participating in, contributing to, and accruing the benefits of geosciences. A change in the culture of our learning and working environments is required to dismantle barriers and promote belonging, accessibility, justice, equity, diversity, and inclusion in our field. Inspired by a session organized at the 2020 Ocean Sciences Meeting, the goal of this paper is to provide a consolidated summary of a few innovative and broadening participation initiatives that are being led by various stakeholders in academia (e.g., students, faculty, administrative leaders) at different institutional levels (e.g., universities, professional societies). The authors hope that the strategies outlined in this paper will inspire the coastal, ocean, and marine science community to take individual and collective actions that lead to a positive culture change.

Lower cardiac output is associated with neurodegeneration among older adults with normal cognition but not mild cognitive impairment - Elizabeth E. Moore; Dandan Liu; Corey W. Bown; Hailey A. Kresge; Deepak K. Gupta; Kimberly R. Pechman; Lisa A. Mendes; L. Taylor Davis; Katherine A. Gifford; Adam W. Anderson; Thomas J. Wang; Bennett A. Landman; et al. (Brain Imaging and Behavior, 2021)

A tropical Australian refuge for photosymbiotic benthic fauna - Zoe T. Richards; Rodrigo Garcia; Glenn Moore; Jane Fromont; Lisa Kirkendale; Monika Bryce; Clay Bryce; Ana Hara; Jenelle Ritchie; Oliver Gomez; Corey Whisson; Mark Allen; et al. (Coral Reefs, 2019)

Prediction of Large Whale Distributions: A Comparison of Presence–Absence and Presence-Only Modeling Techniques - Paul C. Fiedler; Jessica V. Redfern; Karin A. Forney; Daniel M. Palacios; Corey Sheredy; Kristin Rasmussen; Ignacio García-Godos; Luis Santillán; Michael J. Tetley; Fernando Félix; Lisa T. Ballance (Frontiers in Marine Science, 2018)

Exposure of the US Population to Nitrate, Thiocyanate, Perchlorate, and Iodine Based on NHANES 2005–2014 - Lisa M. Corey; Gavin P. Bell; Richard C. Pleus (Bulletin of Environmental Contamination and Toxicology, 2017)

World Squid Fisheries - Alexander I. Arkhipkin; Paul G. K. Rodhouse; Graham J. Pierce; Warwick Sauer; Mitsuo Sakai; Louise Allcock; Juan Arguelles; John R. Bower; Gladis Castillo; Luca Ceriola; Chih-Shin Chen; Xinjun Chen; et al. (Reviews in Fisheries Science & Aquaculture, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Modifier gene study of meconium ileus in cystic fibrosis: statistical considerations and gene mapping results - Ruslan Dorfman; Weili Li; Lei Sun; Fan Lin; Yongqian Wang; Andrew Sandford; Peter D. Paré; Karen McKay; Hana Kayserova; Tereza Piskackova; Milan Macek; Kamila Czerska; et al. (Human Genetics, 2009)

The intercellular adhesin locus ica is present in clinical isolates of Staphylococcus aureus from bacteremic patients with infected and uninfected prosthetic joints - Vance G. Fowler Jr; Paul D. Fey; L. Barth Reller; Anna Lisa Chamis; G. Ralph Corey; Mark E. Rupp (Medical Microbiology and Immunology, 2001)